2021
DOI: 10.1084/jem.20210040
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis of the cellular heterogeneity and interactions in the injured mouse spinal cord

Abstract: The wound healing process that occurs after spinal cord injury is critical for maintaining tissue homeostasis and limiting tissue damage, but eventually results in a scar-like environment that is not conducive to regeneration and repair. A better understanding of this dichotomy is critical to developing effective therapeutics that target the appropriate pathobiology, but a major challenge has been the large cellular heterogeneity that results in immensely complex cellular interactions. In this study, we used s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
186
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(214 citation statements)
references
References 65 publications
26
186
1
1
Order By: Relevance
“…Importantly, there are limited peer-reviewed transcriptomics data available to date. scRNA-seq was used to generate transcriptomics data based on temporal changes post-injury after mouse contusion SCI at 1, 3, and 7 dpi ( Milich et al, 2021 ). Gene Ontology (GO) Enrichment Analysis for differentially expressed genes performed on astrocytes at 1 dpi were “translation” and “biosynthetic processes,” while by 3 dpi astrocytes were defined by “mitochondrial function” and “oxidative phosphorylation,” and at 7 dpi astrocytes were related to “lipid processing” ( Milich et al, 2021 ).…”
Section: Traumatic Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, there are limited peer-reviewed transcriptomics data available to date. scRNA-seq was used to generate transcriptomics data based on temporal changes post-injury after mouse contusion SCI at 1, 3, and 7 dpi ( Milich et al, 2021 ). Gene Ontology (GO) Enrichment Analysis for differentially expressed genes performed on astrocytes at 1 dpi were “translation” and “biosynthetic processes,” while by 3 dpi astrocytes were defined by “mitochondrial function” and “oxidative phosphorylation,” and at 7 dpi astrocytes were related to “lipid processing” ( Milich et al, 2021 ).…”
Section: Traumatic Injurymentioning
confidence: 99%
“…scRNA-seq was used to generate transcriptomics data based on temporal changes post-injury after mouse contusion SCI at 1, 3, and 7 dpi ( Milich et al, 2021 ). Gene Ontology (GO) Enrichment Analysis for differentially expressed genes performed on astrocytes at 1 dpi were “translation” and “biosynthetic processes,” while by 3 dpi astrocytes were defined by “mitochondrial function” and “oxidative phosphorylation,” and at 7 dpi astrocytes were related to “lipid processing” ( Milich et al, 2021 ). Despite numerous remaining questions regarding the extent and functional relevance of temporal astrocyte diversity following CNS traumatic injury, it appears probable that dynamic changes are evident following injury with shifting roles in the evolving injury and recovery processes, hence representing plasticity in response to environmental fluctuations.…”
Section: Traumatic Injurymentioning
confidence: 99%
“…Nevertheless, these results have been reproduced by other teams after contusive SCI [23,24]. Recently, a study, based on single cell experiments, has described the appearance of an astroependymal cell population present only after SCI in mice, confirming the reactivity and the differentiation potential of the ependymal cells in the lesioned spinal cord [25].…”
Section: Cellular Populations Which Constitute the Lesion Scarmentioning
confidence: 58%
“…These results perfectly illustrate the underestimated cellular heterogeneity of the lesioned spinal cord. We can hypothesize that pericytes, astrocytes and ependymal cells are constituted of different subpopulations which will be characterized in the near future due to the increasing development of omics technologies, such as spatial proteomics or single cell RNA sequencing [25,27]. Indeed, recently, single nucleus sequencing technology identified the presence of newborn neurons in an adult uninjured spinal cord.…”
Section: Cellular Populations Which Constitute the Lesion Scarmentioning
confidence: 99%
“…More information can be obtained by scRNA-seq, but most of these studies have been performed on mouse models, which show huge differences with rats, especially in cavitation and scar formation, and is less similar to human SCI progression [60]. ScRNA-seq in mouse SCI acute (1, 3 DPL) and sub-acute (7 DPL) indicated that the main response is mediated by resident and infiltrating immune system and OPC activation [61]. This result is in line with our observations of the activation of ECM reorganization genes in the context of the synaptic plasticity pathway.…”
Section: Discussionmentioning
confidence: 99%